(untitled) (Proceedings of the International Conference on Future of Education, 2022)
Chemistry education in The Gambia is challenged by a lack of laboratory and human resources. The consequences have been unsatisfactory learning outcomes in the Gambian secondary school system. Smartboards, Smart notebook software, and touch-screen laptops were considered to influence learning outcomes. Therefore, a comparison was made between this method and the traditional method. The study used the randomized pre-test-post-test group design to select 284 students by convenient sampling and place them in each experimental and control group. While the experimental group was taught using multifunctional approaches, the social constructivism paradigm, and smart learning objects, the control group was taught using traditional methods, laboratory equipment, and worksheet problem-solving. The effectiveness of the teaching methods was determined by the mean scores on pre-tests and post-tests. Pre-test mean ranks on academic achievement computed using the Mann-Whitney U test indicated no significant difference between the experimental and the control group. However, in the post-test, there was a significant difference (p = 0.003) between the groups, favouring the experimental group. In addition, a higher mean rank was found in the experimental group than in the control group on concept knowledge and application. The results support the current use of modern technology in science teaching and imply that smart technologies can lead to better learning outcomes in the Gambian context if they were to be used extensively in the secondary school system. However, a further study that will determine the level of effectiveness of each of the methods of teaching by comparing the difference between pre-test and post-test scores for each group may be needed in the future, as this will indicate a better measure of the effectiveness of the methods in enhancing students’ academic performances.